High Spinal Anesthesia in Total Knee Replacement - Belinda, Febri Ahmad; Sumaryono, Hery Budi (Faculty of Medicine, Brawijaya University, 2022)
Background: Osteoarthritis (OA) is the most common degenerative disease at people aged 63-70 years. Human ageing is associated with an increase in weakness around the joints, decreased joint flexibility, calcification of cartilage, and decreased chondrocyte function. Total knee replacement (TKR) is performed to treat pain and immobilisation in osteoarthritis patients. This procedure is done with spinal anaesthesia.Case: A 73 years old man diagnosed with bilateral OA and underwent TKR. The patient had left knee pain six months ago with a history of high blood pressure. If blood pressure <160/90 mmHg subarachnoid block was planed. The patient entered the operating room with an intravenous (IV) line of ringer lactate 10 dpm. Preoperatively, the patient was given ranitidine 50 mg IV and ondansetron 4 mg. The anaesthetic agent was hyperbaric bupivacaine 0.5% 15 mg + fentanyl 25 µg; the patient was hemodynamically monitored and maintained with O2 4 lpm. After 45 minutes of spinal anesthesia, the patient experienced respiratory distress, so we placed a masked and intubated the patient with endotracheal tube (ETT) 7.0. It is suspected that the patient had high spinal anesthesia.Conclusion: A 73-year-old man has been subjected to regional spinal anesthesia with total knee replacement surgery. However, spinal anesthesia failed and was converted to general anesthesia with ETT, with a duration of operation of 4 hours, hemodynamically stable, postoperatively the patient was admitted to the high care unit.